Políticas públicas educativas, una revisión sistemática - Vargas Avalos, Evelyn Venecia (2021)
This article makes an analysis of educational policies applying a systematic review of various authors, who deal with different elements such as the assurance of educational quality, in various types of education, both at the secondary level and the higher level and special education, all this according to the public management established by the different State agencies in their respective governments. The main objective is to carry out a study of the educational public policies that different regions of the world make using the methodology established in the Prisma declaration, as a method to inquire about those bibliographic aspects that are related to the title and objectives of this work. Articles based mainly on the search databases in Scopus, Dialnet and Scielo were compiled, resulting in the particularities of said policies in order, through others, to continue delving into this aspect.